2018
DOI: 10.1063/1674-0068/31/cjcp1805126
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical study of potential energy surface in the formation of atmospheric sulfuric acid

Abstract: A new potential energy surface (PES) for the atmospheric formation of sulfuric acid from OH+SO 2 is investigated using density functional theory and high-level ab initio molecular orbital theory. A pathway focused on the new PES assumes the reaction to take place between the radical complex SO 3 ·HO 2 and H 2 O. The unusual stability of SO 3 ·HO 2 is the principal basis of the new pathway, which has the same final outcome as the current reaction mechanism in the literature but it avoids the production and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…SO 3 is considered to be one of the major pollutants present in Earth’s atmosphere because of its role in the formation of atmospheric aerosols and its contributions toward acid rain via formation of sulfuric acid (SA), that is, H 2 SO 4 . SO 3 is mainly formed in atmosphere by gas-phase oxidation of sulfur dioxide (SO 2 ). , In atmosphere, SO 3 rapidly reacts with water to form SA. SO 3 has drawn the attention of atmospheric chemists for a long time because of its pivotal role in the atmospheric acid rain and various nucleation processes. Formation of SA through gas-phase hydrolysis of SO 3 has been extensively studied by various research groups, both experimentally , as well as theoretically. Various investigations suggested that SA formation through the reaction between SO 3 and water monomer (WM) is unfavorable under atmospheric conditions because of high energy barrier (>28 kcal mol –1 ). As a result, the effect of different catalysts, namely, water, , , , hydroperoxy radical, formic acid, , SA (as an auto catalyst), nitric acid, and ammonia (AM), on the hydrolysis of SO 3 , was studied by various research groups. Considering the combined effect of rate constants and catalysts’ concentrations, WM and AM were proposed to have significant contribution in total SA formation in the troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…SO 3 is considered to be one of the major pollutants present in Earth’s atmosphere because of its role in the formation of atmospheric aerosols and its contributions toward acid rain via formation of sulfuric acid (SA), that is, H 2 SO 4 . SO 3 is mainly formed in atmosphere by gas-phase oxidation of sulfur dioxide (SO 2 ). , In atmosphere, SO 3 rapidly reacts with water to form SA. SO 3 has drawn the attention of atmospheric chemists for a long time because of its pivotal role in the atmospheric acid rain and various nucleation processes. Formation of SA through gas-phase hydrolysis of SO 3 has been extensively studied by various research groups, both experimentally , as well as theoretically. Various investigations suggested that SA formation through the reaction between SO 3 and water monomer (WM) is unfavorable under atmospheric conditions because of high energy barrier (>28 kcal mol –1 ). As a result, the effect of different catalysts, namely, water, , , , hydroperoxy radical, formic acid, , SA (as an auto catalyst), nitric acid, and ammonia (AM), on the hydrolysis of SO 3 , was studied by various research groups. Considering the combined effect of rate constants and catalysts’ concentrations, WM and AM were proposed to have significant contribution in total SA formation in the troposphere.…”
Section: Introductionmentioning
confidence: 99%